(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
In the midst of the rapid digitalization era, the presence of sports management information systems has become a crucial and fundamental component in supporting the effectiveness and transparency of modern competition administration. This research is specifically designed to conduct an in-depth investigation and analysis of the satisfaction levels among users of the PSSI Information and Administration System (SIAP PSSI) account. The focus of the evaluation is directed at the system’s implementation within the athlete data management framework for the prestigious 2025 Central Java Soeratin Cup. To achieve this objective, the study adopts a systematic quantitative approach, wherein primary data were collected through the distribution of a structured questionnaire survey based on a 5-point Likert scale. The collected data were subsequently analyzed using descriptive statistical methods to identify central tendencies and response dispersion levels. The results of the data analysis reveal a statistically significant and exceptionally high level of user satisfaction. This is substantiated by a mean score centered at 4.52. This convincing level of satisfaction is further reinforced by the finding of a low standard deviation, recorded at 1.02. Such minimal deviation signifies a strong degree of consensus and response homogeneity among all survey participants, implying that the positive perception of the system is uniformly distributed. Consequently, this finding comprehensively implies that the SIAP PSSI system was not only successfully adopted and well-received by its user community but has also proven to be effective and successful in meeting, and arguably exceeding, the crucial expectations related to its functionality, usability, and overall system performance within the measured context.